Correlation between Anemia and Preeclampsia in Universitas Airlangga Hospital in 2017 - Haris Rasyid Ridho; Muhammad Ilham Aldika Akbar; Widati Fatmaningrum; Budi Santoso (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2021)
Introduction: One of the causes of acute kidney injury that is increasingly soaring is preeclampsia syndrome. Globally, the maternal mortality rate reaches 287,000 per year, and preeclampsia is a major contributor. From East Java Provincial Health Office data, per 100,000 pregnancies, 114 had preeclampsia syndrome. Anemia is one of the highest causes of maternal death, the global prevalence of anemia in pregnant women reaches 55.9%. There have not been many significant studies on the effect of anemia with the incidence of preeclampsia.Methods: This was observational analytic study with a case and control design which used a chi-square and fisher exact measurement tool. The data samples were patients of pregnant women who had preeclampsia syndrome categorized as cases, and those who did not have preeclampsia were categorized as controls. The data has been obtained from medical records; these include ages, the number of parities, the number of pregnancies, body mass index (BMI), the number of childbirths, types of preeclampsia, and hemoglobin levels. The data has been obtained from the result of the medical record observations that were processed and analyzed in descriptive of statistics which used percentage and cross tab.Results: The case study group or preeclampsia pregnant women who experienced anemia were 34 patients or 50% of 68 pregnant women and in the control group were 53 patients or 39% of anemia patients out of 136 patients. The chi-square statistical test obtained values (p = 0.133). The samples needed were 68 case groups and 136  cases as controls.Conclusion: There was no relationship between anemia and preeclampsia.